2006
DOI: 10.1620/tjem.208.235
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Hypofunction in Preschool Children with Short Nocturnal Sleep

Abstract: Preschool children with sleep deficit may suffer from autonomic symptoms or hypotension. Heart rate variability, reflecting cardiac parasympathetic and sympathetic activities, and blood pressure were assessed to clarify the effects of nocturnal sleep duration on cardiac autonomic function in 134 preschool children aged 5 and 6 years. Parents reported their children's typical bedtimes and wake times for weekdays. In the children, the mean nocturnal sleep duration (± standard deviation) was 575 ± 42 min. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…In the present study, the average total sleep duration ( ± SD) on weekdays, calculated from nocturnal sleep duration and mandatory nap time, was 624 ± 57 min, and this was of course longer than the nocturnal sleep duration (575 ± 42 min) in Japanese preschool children at the same ages (21). The average total sleep duration in our subjects at ages 5-6 years is consistent with those in the U.S. (2), Switzerland (7), and Iceland (23).…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…In the present study, the average total sleep duration ( ± SD) on weekdays, calculated from nocturnal sleep duration and mandatory nap time, was 624 ± 57 min, and this was of course longer than the nocturnal sleep duration (575 ± 42 min) in Japanese preschool children at the same ages (21). The average total sleep duration in our subjects at ages 5-6 years is consistent with those in the U.S. (2), Switzerland (7), and Iceland (23).…”
Section: Discussioncontrasting
confidence: 46%
“…We have already reported that SBP, together with cardiac autonomic activities, was significantly decreased in preschool children with short nocturnal sleep ( < 600 min) as compared to those with long nocturnal sleep ( ≥ 600 min), but the SBP did not have any close relation to nocturnal sleep duration in using multiple regression analysis with independent variables of age, sex, Kaup index, and institute (21). By contrast, the link between total sleep duration and SBP, as mentioned above, was statistically significant, albeit the change in the SBP was small (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations